Analysis of the impact of Hasanudin Petrosea Road infrastructure improvement on the economic activities (production, distribution, and income) of the surrounding community - Serlina Masua; Julius Ary Mollet (Goodwood Publishing, 2025)
Purpose: This study aimed to analyze the impact of the Hasanudin-Petrosea road infrastructure improvement on the economic activities of surrounding communities in Mimika Regency, focusing on production, distribution, and income levels. Research/methodology: Using a quantitative descriptive approach, primary data were gathered through field observations, structured questionnaires, and documentation. Respondents were selected using purposive sampling, and data were analyzed using descriptive statistical methods to identify changes in economic activities before and after the infrastructure development. Results: The findings indicate a significant positive impact on the local economy of the area. Most respondents reported increased production capacity, smoother distribution processes, and higher income levels following road improvements. Improved accessibility has stimulated the growth of small businesses, such as workshops, food stalls, and kiosks, along the upgraded road segment. Conclusions: The improvement of Hasanudin–Petrosea Road infrastructure has positively influenced local economic activities by enhancing production efficiency, supporting the distribution of goods, and increasing the household income. It has also encouraged the development of small businesses along the corridor. To sustain these benefits, continuous infrastructure maintenance and integrated economic planning are necessary to ensure the long-term prosperity of local communities. Limitations: This study was limited to one geographic location and a relatively small sample size, which may not fully reflect the broader regional impact. The analysis also does not address the long-term sustainability or maintenance aspects. Contribution: This study adds to the literature on infrastructure-led local economic development by providing empirical evidence on how improved road access stimulates production, distribution efficiency, and income while serving as a policy reference for future infrastructure planning in underdeveloped regions.